A Qualitative Inquiry Into the Challenges of Medical Education for Retention of General Practitioners in Rural and Underserved Areas of Iran - Delavari, Sajad (J Prev Med Public Health, 2016)
OBJECTIVES: General practitioners (GPs) retention in rural and underserved areas highly effects on accessibility of healthcare facilities across the country. Education seems to be a critical factor that affects GPs retention. Thus, the present study aimed at inquiry into medical education challenges that limit their retention in rural and underserved areas. METHODS: A qualitative approach was applied for the aim of this study. Data were gathered via 28 semi-structured interviews with experts at different levels of Iran’s health system as well as GPs who retained and refused to retain working in rural settings. Interviews mainly were performed face-to-face and in some cases via telephone during 2015 and then coded and analyzed using content analysis approach. RESULTS: Iran’s medical education is faced with several challenges that were categorized in four main themes including student selection, medical students’ perception about their field of study, education setting and approach, curriculum of medical education. According to experts this challenges could results in making GP graduates disinterested for practicing in rural and underserved areas. CONCLUSIONS: Challenges that were found could have negative effects on retention. Modification in student’s perception about rural practice could be done via changing education setting and approach and curriculum. These modifications could improve GPs retention in rural and underserved areas.